Phenytoin-induced rickets in a ten-year-old girl with hypothyroidism - Teziç, Tahsin; Arslanoğlu, Mehmet; Gedik, Yusuf; Nuhoğlu, Asiye (The Turkish Journal of Pediatrics, 1983)
A 10-year-old epileptic and hypothyroidic girl who developed rickets while on phenytoin treatment is presented. Calcium and bone metabolism in the presence of both hypothyroidism and rickets is discussed.
Keywords: hypothyroidism; phenytoin; rickets